Treating Psoriatic Arthritis By TNF –Α Inhibitors: A Case Study: Life Science-Skin diseases - Nadezhda Vladimirovna, Zhuravleva; Olga Viktorovna, Sharapova; Liudmila Ivanovna, Gerasimova; Valentina Nikolaevna, Diomidova; Tatiana Lvovna, Smirnova; Nadezhda Dmitrievna, Ukhterova; Luiza Mikhailovna, Karzakova; Anastasia Vladimirovna, Arkhipova; Svetlana Alexandrovna, Yastrebova (International Journal of Life Science and Pharma Research, 2022)
Psoriatic arthritis (PsA) is a heterogeneous seronegative chronic inflammatory spondyloarthritis associated with psoriasis. Doctors consider PsA hard in complex treatment. The purpose of the study is to perform the analysis of clinical data and to identify the features of psoriatic arthriti's and selecting drug therapy.The patient's condition clinical assessment has carried out by using clinical, laboratory and instrumental methods with calculating the Psoriasis Area and Severity Index (PASI), the CASPAR diagnostic criteria and the genetically engineered biological drugs treatment.In the clinical case we studied, a patient with a history of psoriasis has first diagnosed with widespread skin psoriasis at the age of 12, when he carried out medicamentous therapy combined with PUVA. Despite the use of glucocorticosteroids, no complete regression of psoriasis has observed, and the PASI score was 35.3- 36.3 points. At the age of 30, the patient developed lower back pains, enthesitis, the PASI score was of 37.1 points. Nonsteroidal anti-inflammatory drugs were added to the treatment. At the age of 42, he was diagnosed with psoriatic arthritis, activity III, stage II, dactylitis, enthesites, the PASI index was 31.3 points; right-sided active sacroiliitis - radiologically stage 1 (BASDAI 4.2 points), FCS 2-3". According to the CASPAR criteria, 4 points were obtained at the time of the disease diagnosis (current psoriasis - 2 points, familial psoriasis - 1 point, negative rheumatoid factor - 1 point). In 2016, at the age of 48, Adalimumab therapy has started according to the scheme in combination with Methotrexate, as a result it was possible to achieve psoriatic arthritis remission and the skin rashes' regressed and 0 PASI score.The psoriatic arthritis therapy with the use of Adalimumab - TNF-α - inhibitor contributed to the disease's long-term stable remission and completed the psoriatic skin rashes regression.